Tryptophanyl-tRNA synthetase and its role in the incorporation of new intrinsic fluorescent probes into proteins. - Hogue, Christopher Warren Victor. (University of Ottawa (Canada), 1994)
Fluorescence spectroscopy can reveal insights into the structure, function and dynamics of proteins using the intrinsic fluorescence of tryptophan (Trp) residues. Time-resolved fluorescence is uniquely sensitive to the local microenvironment of Trp residues. This methodology is widely used, yet extensions allowing the further study of protein interactions are desired. Tryptophan analogs are targeted as new intrinsic probes, since their structures may camouflage them sufficiently to trick the relevant protein synthesis mechanisms to allow their incorporation into proteins. The specificity of a single enzyme, tryptophanyl-tRNA synthetase (TrpRS; E.C. 6.1.1.2), is the key to success for biosynthetic Trp analog incorporation. TrpRS catalyzes the ATP activation of Trp, and the subsequent aminoacylation of tRNATrp, prior to ribosomal protein synthesis. Bacillus subtilis TrpRS has a single conserved and essential Trp-92 residue in each of its symmetrical alpha-2 subunits. The fluorescence of this Trp was very useful for investigating the TrpRS mechanism, together with the nonfluorescent isomorphous analog 4-fluorotryptophan as substrate. A tryptophanyl-5'-adenylate dependent quenching of Trp-92 fluorescence was observed, consistent with a local alpha-helix formation, placing a conserved Cys residue in quenching proximity to the Trp-92 fluorophore. This corresponds with the recent crystal structure of the homologous B. stearothermophilus TrpRS. Titrations while monitoring Trp-92 fluorescence revealed that the TrpRS dimer undergoes a concerted conformational change, virtually complete with the reaction of one subunit. This change seems necessary since this very small enzyme could only bind the relatively large tRNATrp substrate through interactions with both subunits. Potentially useful Trp analogs for fluorescence studies were examined to determine if they were TrpRS substrates. 5-hydroxytryptophan (5HW) and 7-azatryptophan (7AW) were studied both as TrpRS substrates, and as biosynthetically incorporated replacements of Trp-92. Methodology for efficient incorporation of these normally toxic Trp analogs is demonstrated. 7AW was shown to be very sensitive to solvent exposure, as its inclusion into a buried region of the protein causes large increases in its fluorescence yield. 7AW is recognized as having particular utility for the study of protein folding. Observations of the time-resolved fluorescence behaviour of Trp and 5HW in the same protein microenvironment are of consequence for fluorescence theory, as they indicate that the current assumptions regarding radiative properties may require modification. By combining insights from both the crystal structure and these intrinsic fluorescence studies with both Trp and the analogs, a clearer picture of the mechanism of TrpRS was obtained. Prior to this study, the role of the essential Trp-92 was not understood in terms of the mechanism of TrpRS. This study demonstrates Trp-92 is crucial for both TrpRS conformational stability and for its very dynamic mechanism which involves large, substrate-dependent conformational changes.
Keywords: Chemistry, Biochemistry.